Gambaran Perilaku Kebersihan Organ Genitalia Eksterna Siswi Kelas X Sekolah Menengah Atas Negeri 1 Kawangkoa - Lampus, Benny S.; Pandelaki, August J.; Tapparan, Fitrianti (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Maintaining cleanliness external genital organs is an early effort maintaining reproductive health. If behavior of External genital organs hygiene is not good, can cause infections of the reproductive organs. In fact the knowledge and awareness of adolescent girls on reproductive health is very low. The research objective was to determine the behavior description of external genital organs hygiene grader X student of SMA Negeri 1 Kawangkoan. This study uses descriptive quantitative cross sectional approach. The research sample was 50 students taken by simple random sampling. Data retrieval is done by filling out the questionnaire and analysised with univariate analysis.Â Â  The majority of respondents knowledge fit in either category, that is 32 respondents (64%), while 18 respondents (36%) poor. Good attitude either (54%), and measures either (52%). They should improve hygiene behavior genital organs eksternal. Keywords: behavior, cleanliness external genital organ.